The Influence of Online Reviews on Consumer Purchase Decisions - Sari, Meli Yumita; Septyani, Rilis; Mayasari, Mayasari; Ulfah, Fadilla; Arief, Hidayatul (The Future of Education Journal, 2026)
This study analyzes the influence of online reviews on consumer purchase decisions in digital marketing, to understand how consumer-generated information on digital platforms affects buying behavior. A quantitative approach was employed, collecting data via questionnaires from 15 respondents, analyzed using Pearson correlation test. Results reveal a very strong positive influence (r = 0.915), where better online review quality heightens purchase tendency. The coefficient of determination at 83.7% indicates that online reviews predominantly drive purchase decisions, with 16.3% influenced by other factors. Findings strengthen the electronic word-of-mouth (e-WOM) concept and digital consumer behavior. Implications suggest businesses manage reviews to enhance consumer trust, product reputation, and sales. This research contributes to the development of literature and business practices in the digital era.